A multicentre evaluation of the diagnostic efficiency of serological investigations for C1 inhibitor deficiency. Issue 2 (1st February 2002) - Gompels, M M; Lock, R J; Morgan, J E; Osborne, J; Brown, A; Virgo, P F
Abstract : Aim: To determine the diagnostic efficiency of assays routinely used in the investigation of hereditary angio-oedema. Methods: Over a four year period, 1144 samples were received for analysis from 907 patients suspected of C1 inhibitor deficiency. Analyses were performed for C4 and C1 inhibitor (functional and immunochemical). Notes were reviewed retrospectively on patients with low serological indicators to determine diagnosis. Results: These are the first data to indicate the sensitivity, specificity, and predictive values of the assays most frequently used to screen for C1 inhibitor deficiency. A combination of low C4 and low C1 inhibitor function has 98% specificity for C1 inhibitor deficiency in this population and a 96% negative predictive value, and is thus a very effective screen. All patients with untreated C1 inhibitor deficiency had a low C4 value. Conclusions: All patients considered for a diagnosis of C1 inhibitor deficiency should have serum examined to measure both C4 and functional C1 inhibitor. If either is normal at presentation this essentially excludes a diagnosis of C1 inhibitor deficiency. These tests can be performed sequentially. If C4 is normal it is not necessary to proceed to C1 inhibitor analysis. If C1 inhibitor function and C4 are both low then a repeat sample should be obtained to confirm the findings.